Role of HCA2 (GPR109A) in nicotinic acid and fumaric acid ester-induced effects on the skin - Hanson, Julien; Gille, Andreas; Offermanns, Stefan (Pharmacology & therapeutics, 2012)
Nicotinic acid (NA) and fumaric acid esters (FAE) such as monomethyl fumarate or dimethyl fumarate are drugs that elicit a cutaneous reaction called ﬂushing as a side effect. NA is used to reduce progression of atherosclerosis through its anti-dyslipidemic activity and lipid-independent mechanisms involving immune cells, whereas FAE are used to treat psoriasis via largely unknown mechanisms. Both, NA and FAE, induce ﬂushing by the activation of the G-protein-coupled receptor (GPCR) Hydroxy-carboxylic acid receptor 2 (HCA2, GPR109A) in cells of the epidermis. While the wanted effects of NA are at least in part also mediated by HCA2, it is currently not clear whether this receptor is also involved in the anti-psoriatic effects of FAE. The HCA2‐mediated ﬂushing response to these drugs involves the formation of prostaglandins D2 and E2 by Langerhans cells and keratinocytes via COX-1 in Langerhans cells and COX-2 in keratinocytes. This review summarizes recent progress in the understanding of the mechanisms underlying HCA2-mediated ﬂushing, describes strategies to mitigate it and discusses the potential link between ﬂushing, HCA2 and the anti-psoriatic effects of FAE.
Im Titel ist die Zahl 2 tiefgestellt
Available online 26 June 2012
Gesehen am 26.07.2018